Case Report: All That Glisters Is Not* Cancer - Tirelli, Claudio; Bortolotto, Chandra; Morbini, Patrizia; Stella, Giulia Maria (Frontiers in Medicine, 2020)
Properly performed staging in NSCLC is necessary to avoid wrong therapeutic decisions. Here we present a case who presented as advanced NSCLC, but ultimately was composed by two different and rare pathologies. The first is a TTF-1 positive axillary lymphnode that could be defined either as an unusual isolated differentiated cancer of unknwon primary or as an even rarer case of ectopic lung epithelium which underwent malignant transformation. The second is sarcoidosis, or a sarcoid-like alteration, in remission after oral steroids. The main implication of a correct diagnosis regards patient outcome and the avoidance of toxic inappropriate systemic chemotherapy